Evaluating students assessment group project using fuzzy analytic hierarchy process (FAHP) / Nurul Suhada Aziz ... [et al.] - Aziz, Nurul Suhada; Rozi, Farah Farhana; Ghaming, Siti Nurfatin Farhana; Ridzuan Ishak, Natasya Adlina (2022)
In education, evaluation plays a major role in determining performance. Artificial intelligence systems have become popular in recent years to understand the process of human thinking and to move it to virtual environments. Evaluating a student's project can be effective in improving student performance. By combining qualitative and quantitative factors, fuzzy logic is used to express human thinking in mathematical concepts. It has become one of the most preferred methods in finding a solution to decision-making problems. The fuzzy Analytic Hierarchy Process (FAHP) is one of the multi-criteria decision-making (MCDM) methods based on fuzzy logic. In this case, FAHP has been proposed for evaluating students' group project assessments by determining the main criteria and sub-criteria used in the evaluation system. Three projects were selected based on four main criteria and 16 sub-criteria. A questionnaire was constructed based on the selected criteria. Three experts were requested to answer the questionnaire. The pairwise comparison was developed based on the opinion of the experts. Later, the main criteria and sub-criteria were formed in a mathematical number using a linguistic variable in a triangular fuzzy number (TFN). Ranking was formed from the result of every project. The result is compared by using a manual system and FAHP. According to the findings of this study, Alternative 3 has the highest weight compared to the others and similar to the manual rubric system.